Elaboración de un manual de funcionamiento, mantenimiento de los equipos cámara de flujo laminar e incubación del laboratorio de biotecnología de la reproducción - Jaramillo Maza, Diego Michell (2015)
The veterinary medicine career is one of the major which allows to contribute on the problem solving about the livestock sector and provide a service in which people may resolve problems that appear on this sector daily. These types of manuals are addressed for an efficient management, correct operation and laboratory equipment maintenance helping out as a substitute or supplement to the manufacturer’s manual. Within the practice guide was considered three fundamental steps which are related on biotechnology laboratory equipment of reproduction. The first part is related on the equipment performance and operating being a very important aspect that everybody has to take into account. The second and third part have links with the maintenance and the equipment renovation plan as well. Which is presented to the reply of what? when? and how? each action is done. The equipment manual has been developed to give support and provide academic information to the students and teachers in the livestock field....